Whole-genome analysis and secondary metabolites production of a new strain Brevibacillus halotolerans 7WMA2: A potential biocontrol agent against fungal pathogens. (November 2022) - Le Han, Ho; Jiang, Lingmin; Thu Tran, Thi Ngoc; Muhammad, Neak; Kim, Song-Gun; Tran Pham, Vinh Phu; Ng, Yan Jer; Khoo, Kuan Shiong; Chew, Kit Wayne; Phuong Nguyen, Thi Dong
Abstract: The extensive usage of synthetic fungicides against fungal diseases has caused adverse impacts on both human and agricultural crops. Therefore, the current study aims to establish a new bacterium 7WMA2, as a biocontrol agent to achieve better antifungal results. The strain 7WMA2 was isolated from marine sediment, displayed a broad spectrum of several fungi that includes Alternaria alternata, Cladosporium sp., Candida albicans, Fusarium oxysporum, Trichosporon pullulans, and Trichophyton rubrum . The 16S rRNA phylogeny inferred that strain 7WMA2 was a member of Brevibacillus . The phylogenetic and biochemical analyses revealed that the strain 7WMA2 belongs to the species of Brevibacillus halotolerans . The complete genome sequence of Brevibacillus halotolerans 7WMA2 consists of a circular chromosome of 5, 351, 077 bp length with a GC content of 41.39 mol %, including 4433 CDS, 111 tRNA genes, and 36 rRNA genes. The genomic analysis showed 23 putative biosynthetic secondary metabolite gene clusters responsible for non-ribosomal peptides, polyketides and siderophores. The antifungal compounds concentrated from cell-free fermentation broth demonstrated strong inhibition of fungi, and the compounds are considerably thermal stable and adaptable to pH range 2–12. This complete genome sequence has provided insight for further exploration of antagonistic ability and its secondary metabolite compounds indicated feasibility as biological control agents against fungal infections. Graphical abstract: Image 1 Highlights: A new bacteria strain Brevibacillus halotolerans 7WMA2 was isolated. Effective antifungal effect using biocontrol agent over chemical fungicides. Complete genome was determined for antifungal biosynthetic gene clusters. Genomic analysis revealed 23 putative biosynthetic secondary metabolite gene clusters. Cell-free and partial purified extracts of strain 7WMA2 retained activities after intense exposure.